Aortic valve papillary fibroelastoma in a cat: Case report - Civelek, Turan; Erkoç, Ender; Alpay, Ömer Cankan (Afyon Kocatepe Üniversitesi)
Cardiac tumors are rare in cats. Usually the diagnosis can be made on echocardiographic examination. Papillary fibroelastoma in this case is a primary cardiac tumor and is histopathologically defined as benign. However, these types of tumors carry the risk of thromboembolism and may cause complications such as stroke or infarction. In these types of the cases the symptoms are not specific and may vary depending on the size or structure of the mass. In the report a case of papillary fibroelastoma identified echocardiographically in a male tabby cat is discussed.

Kardiyak tümörlere kedilerde nadir rastlanır. Teşhis genellikle ekokardiyografik muayene ile yapılır. Bu vakadaki Papillar Fibroelastoma primer bir kalp tümörüdür ve histopatolojik olarak iyi huylu olarak tanımlanır. Bununla birlikte bu tip tümörler tromboemboli riski taşır, felç ya da enfarktüs gibi komplikasyonlara sebebiyet verebilir. Bu tip vakalarda belirtiler spesifik değildir ve kitlenin boyutu veya yapısı ile bağlantılı olarak değişkenlik gösterebilir. Sunulan raporda tekir ırkı erkek bir kedide ekokardiyografik olarak tanımlanan papiller fibroelastoma olgusu tartışıldı.
Bir kedide aort kapağı papiller fibroelastomu: Vaka raporu
Keywords: Cardiac; Echocardiography; Feline; Fibroelastoma; Tumor; Kardiyak; Ekokardiyografi; Kedigiller; Fibroelastoma; Tümör